(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Seasonal and spatial distribution of zooplankton communities in relation with some physico-chemical parameters in the south eastern coastal waters of Bangladesh was carried out from January 2016 to November 2016. Zooplankton samples were collected from seven different selected stations covering various ecosystems, viz.: Riverine (Bhola, Barishal & Chandpur), Offshore Island water (Sandwip & Hatia) and Nearshore (Cox’s bazar & Naf River) regions. In total 33 genera were recorded during sampling periods and the highest abundance of zooplankton were recorded at Naf River (331.318 ind/m3) and the lowest at Chandpur (22.6414ind/m3) during post-monsoon. In pre-monsoon the highest abundance was recorded at Sandwip (31.49435ind/m3) and the lowest at Bhola (8.239854ind/m3). During monsoon the highest abundance was recorded at Cox’s Bazar (51.64085ind/m3) and the lowest at Barishal (4.389972ind/m3). A total of 24, 22 and 32 individuals (genera) of zooplankton identified during monsoon, pre-monsoon and post-monsoon respectively from all sampling stations. Calanoida, Cyclopoida, Fish larvae, Lucifer and Shrimp Zoea were common in every sampling station. Dictoyptera was the only species found in marine water. The statistical analysis of water quality parameters as temperature, pH, salinity, transparency, DO, TDS and TSS indicated the substantial relationship with seasonal and spatial distribution, diversity and abundance of zooplankton. Diversity index also indicated seasonal and spatial variation of zooplankton communities in the south eastern coastal waters of Bangladesh. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):95-119, 2020